Impact of Vertical Integration Strategies on Environmental, Social, and Governance Sustainability: Policy Implication for Oil and Gas Energy Sector - Ali M.K. (2023)
This research study examines the impact of vertical integration on sustainability in the oil and gas industry. We have analyzed a sample dataset about oil and gas companies from the top ten oil-producing countries spanned over 10 years (2011–2020). Using the panel data regression technique, the results confirm that vertical integration helps improve sustainability and its three components, i.e., environmental, social, and governance, in the oil and gas sector. We have identified that firm’s size, age, and gross domestic production (GDP) positively related to oil and gas industry sustainability. At the same time, oil prices, firm risk, energy transition, and geopolitical risk negatively affect sustainability. The policy implications are essential for oil and gas firms’ management and oil-producing and oil-exporting countries’ policymakers and regulatory authorities.